ANTERIOR TALOFIBULAR LIGAMENT (ATFL) RECONSRUCTION WITH MODIFIED BROSTROM-GOULD TECHNIQUE USING FIBER WIRE - Andre Triadi Desnantyo; Mouli Edward; Asyumaredha Asyumaredha (Journal Orthopaedi and Traumatology Surabaya, 2019)
Background: The incident of ankle sprain reported 1 of 10.000 case each day. The most incident was male about 22-24 year and sport active. We reported 2 cases (15 years old female and 21 years old male) both of them played routine basketball and futsal.